Air Zam-zam dalam Perspektif Hadis dan Sains: Upaya Mendamaikan Agama dan Sains - Holisatur Rahma; Elok Ayu Nandari; Alfina Wildatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Zam-Zam water is water that appeared during the period of Prophet Ismail AS., long before the birth of Prophet Muhammad SAW. Zam-zam water has received direct testimony and justification from the Prophet Muhammad as the best water on earth which contains many benefits. Explicitly, the properties of Zam-Zam water are contained in the hadith, which is considered authentic according to the scholars. This article, in an integrative-interconnective manner, tries to examine the existence of Zam-Zam water through a hadith perspective and a scientific perspective. From a hadith perspective, zam-zam water will be studied using several hadith critical methodologies, both in terms of the text of the hadith (matn) and the transmission of the narrator (sanad). Meanwhile, through a scientific approach, Zam-Zam water will be researched more deeply so that a scientific fact can be found that the substances contained and the molecules that are arranged in Zam-Zam water are better than other substances or water molecules. In this article, this will be proven, among other things, by the results of research by Masaru Emuto, a water expert from Japan, regarding the power of water in general, the magic of Zam-Zam water, and the beauty of the crystals that Zam-Zam water forms. So, the Prophet Muhammad’s justification for Zam-Zam water is embodied by the truth of modern scientific research facts. So it can be said that the agenda to reconcile religion and science is not in vain.